The English Railway and Canal Commission of 1888 - McLean, S. J. (Quarterly Journal of Economics, 1905)
Journal Article The English Railway and Canal Commission of 1888 Get access S. J. McLean S. J. McLean Leland Stanford Jr. University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 20, Issue 1, November 1905, Pages 1–58, https://doi.org/10.2307/1882554 Published: 01 November 1905